Sosialisasi mitigasi bencana: aman dari bencana tanah longsor dan luapan air (AMERTA) - Pratama, Reza Hardian; Purwoko, Eko; Husna, Nurul; Julian, Aqlifa Hanif (JOURNAL of Public Health Concerns, 2025)
Background: Indonesia’s complex topography, geology, and climate make hilly areas such as Karang Rejo Village in Ulubelu Subdistrict, Tanggamus Regency highly vulnerable to landslides and flash floods. Steep slopes, unstable soil conditions, unsustainable land use practices, and unmanaged household waste accumulation contribute to disaster risk and environmental pollution. Open burning of waste further exacerbates health risks due to the emission of toxic substances and fine particulates. Limited waste processing facilities compel residents to locate disposal sites on the village outskirts, increasing both financial burdens and environmental impacts. Purpose: Improving the capacity of the Karang Rejo Village community in mitigating landslide and flood risks through integrated disaster education, as well as introducing and testing the effectiveness of environmentally friendly waste incineration tools. Method: The community service activity themed "Safe from Landslide and Water Hazards" was held on August 27, 2025, at the multi-purpose building Village Hall of Karang Rejo, Ulubelu Subdistrict, Tanggamus Regency, with participants including the Village Head, Village Secretary, BHP Chairperson, Heads of Hamlets 1–6, and local residents. The implementation combined persuasive, educational, and participatory approaches through a seminar on landslide and flood mitigation, introduction of low-smoke waste incinerators, interactive discussions, demonstrations using repurposed drums as burning tools, and hands-on training based on a practical guidebook. A final evaluation was conducted to assess the strengths and weaknesses in terms of both process and outcomes. Results: The activity began with a needs assessment identifying landslide and flood-prone areas as well as the local waste management system. Based on these findings, the work group’s team designed and disseminated low-smoke waste incinerators along with a disaster mitigation education package through seminars, practical demonstrations, interactive discussions, and guidebooks. Residents gained understanding of early signs of landslides and floods, the impact of waste accumulation on water overflow, and procedures for constructing and using the incinerator. The symbolic handover of the incinerator to the village head and the community’s enthusiastic response marked the success of an integrated approach in enhancing environmental awareness and disaster resilience. Conclusion: The activity successfully enhanced community awareness, skills, and preparedness in mitigating landslides, floods, and environmental management. The combination of disaster mitigation outreach and the innovation of low-smoke waste incinerators strengthened residents’ active role in preventing risks stemming from human behavior. The incinerator proved effective in reducing smoke emissions, odors, and heat radiation, thereby supporting healthier and more sustainable household waste management. Suggestion: Recommended follow-up actions include advanced training and the development of low-smoke waste incinerators equipped with integrated filtration systems to more effectively reduce pollution. Strengthening intensive collaboration with the Regional Disaster Management Agency (RDMA) and the Environmental Agency is essential to ensure program sustainability and expand its positive impact on the community. Keywords: AMERTA; Disaster mitigation; Environmental health; Flood; Landslide Pendahuluan: Indonesia dengan karakteristik topografi, geologi, dan iklimnya yang kompleks menjadikan wilayah berbukit seperti Desa Karang Rejo di Kecamatan Ulubelu, Kabupaten Tanggamus, sangat rentan terhadap tanah longsor dan banjir bandang. Lereng curam, kondisi tanah labil, penggunaan lahan yang kurang konservatif, serta akumulasi sampah rumah tangga yang tidak terkelola memicu kerawanan bencana dan pencemaran lingkungan. Praktik pembakaran sampah terbuka menambah risiko kesehatan akibat emisi zat beracun dan partikel halus. Keterbatasan fasilitas pengolahan sampah memaksa masyarakat menempatkan TPA di pinggiran desa, meningkatkan beban biaya dan dampak lingkungan. Tujuan: Meningkatkan kapasitas komunitas Desa Karang Rejo dalam mitigasi risiko tanah longsor dan banjir melalui edukasi bencana terintegrasi, serta memperkenalkan dan menguji efektivitas alat pembakaran sampah yang ramah lingkungan. Metode: Kegiatan pengabdian masyarakat bertema "Aman dari Bencana Tanah Longsor dan Air (AMERTA)" dilaksanakan pada 27 Agustus 2025 di GSG Balai Desa Karang Rejo, Kecamatan Ulubelu, Kabupaten Tanggamus, dengan peserta meliputi Kepala Pekon, Sekretaris Desa, Ketua BHP, Kepala Dusun 1–6, dan warga setempat. Pelaksanaan menggabungkan pendekatan persuasif, edukatif, dan partisipatif melalui seminar mitigasi tanah longsor dan banjir, pengenalan tong pembakar sampah minim asap, diskusi interaktif, demonstrasi pemanfaatan drum bekas sebagai alat pembakaran, serta pelatihan praktik berbasis buku panduan. Evaluasi akhir diadakan untuk menilai kelebihan dan kekurangan dari segi proses maupun hasil kegiatan. Hasil: Kegiatan diawali dengan analisis kebutuhan yang mengidentifikasi titik rawan longsor, banjir, dan sistem pengelolaan sampah lokal. Berdasarkan temuan tersebut, tim KKN merancang dan menyosialisasikan tong pembakar sampah minim asap serta paket edukasi mitigasi bencana melalui seminar, demonstrasi praktis, diskusi interaktif, dan buku panduan. Warga memperoleh pemahaman tentang tanda awal longsor dan banjir, dampak tumpukan sampah pada luapan air, serta prosedur pembuatan dan penggunaan alat pembakar. Penyerahan simbolis tong pembakar kepada kepala pekon dan respons antusias masyarakat menandai keberhasilan pendekatan terpadu dalam meningkatkan kesadaran lingkungan dan ketahanan bencana komunitas. Simpulan: Kegiatan berhasil meningkatkan kesadaran, keterampilan, dan kesiapsiagaan masyarakat dalam mitigasi tanah longsor, banjir, dan pengelolaan lingkungan. Kombinasi sosialisasi mitigasi bencana dan inovasi alat pembakar sampah minim asap memperkuat peran aktif warga dalam pencegahan risiko yang bersumber dari perilaku manusia. Alat tersebut terbukti efektif mengurangi emisi asap, bau, dan radiasi panas, sehingga mendukung pengelolaan sampah rumah tangga yang lebih sehat dan berkelanjutan. Saran: Rekomendasi tindak lanjut meliputi pelatihan lanjutan dan pengembangan alat pembakar sampah minim asap dengan sistem filtrasi terpadu untuk menekan polusi lebih efektif. Kolaborasi intensif dengan BPBD dan Dinas Lingkungan Hidup perlu diperkuat guna menjamin keberlanjutan program dan memperluas dampak positif bagi masyarakat.